From policy frameworks to classroom realities: Analyzing the role of academic tracking in perpetuating educational inequality - Morton , Tabitha S.M. (American Journal of Education and Learning, 2025)
This study examines the Foundation School Program (FSP), a policy designed to improve access to academic tracks and provide students with greater flexibility in their educational pathways. The goal is to evaluate whether the FSP effectively prepares students for the workforce or higher education while addressing systemic inequities in public education. The study utilizes data from the Texas Education Agency covering over 1,200 school districts and applies negative binomial regression analysis to assess the FSP’s impact on African American, Hispanic, and white students. By analyzing enrollment patterns and outcomes, the study investigates whether the policy fosters equitable access to academic tracking programs. Despite increasing student and parent choice in academic tracking, the FSP does not eliminate racial disparities in access to specialized academic tracks. The policy fails to address underlying funding inequities and systemic barriers that disproportionately impact marginalized students. The findings suggest that the FSP mitigates racial disparities in academic tracking. Without structural reforms, the program remains ineffective in achieving equitable access to educational opportunities. This study provides policymakers and administrators with actionable recommendations to enhance equity in academic tracking. These insights can inform policy reforms in other states, regions, and countries with similar public education systems.